Specyfika semantyki frazeologizmów genderowych (na materiale języków wschodnio- i zachodniosłowiańskich) - Kedron, Katerina (Studia Rossica Posnaniensia, 2017)
This study is an attempt to show how the “gender” semantics of fixed expressions form and what the function of the gender component is in this process. An analysis of the language material shows that there are several cases of modification of “gender” semantics of idiomatic phrases: changes in the phrase’s connotation (there are distinctions between utterances with the same structure in one language or between similar cases in different languages); the change of the referent from male to female (or vice versa) or to the common human meaning etc. It is also shown that the role of the gender component is intrinsic to semantic processes.